Capable, splendorous and unequal: international media portrayals of Brazil during the 2014 World Cup. Issue 4 (3rd April 2019) - Graeff, Billy; Monteiro Gutierrez, Diego; Sardá, Thais; Bretherton, Paul; Bettine, Marco
Abstract: This article examines how Brazil was perceived internationally during the 2014 World Cup (2014WC), for which one of Brazil's perceived objectives was to enhance its international image to play a more significant role on the world stage. Nine media outlets' coverage of the 2014WC was analysed using the website Alexa. These outlets published 699 articles about diverse themes relating to Brazilian society. The outlets studied considered the event a success overall and emphasised Brazil's natural beauty, but raised concerns about social problems such as inequality. We conclude that the 2014WC updated but did not fundamentally alter Brazil's international image.